Effectiveness of development of diva learning management system models on Algorithm and Programming Mathematics Course - Muchlis, Lita Sari; Rukun, Kasman; Krismadinata, Krismadinata (Jurnal Pendidikan Teknologi Kejuruan, 2020)
The development of the DIVA Learning Management System learning model is an increase in student understanding based on problems because learning algorithms and programming is indicated to be low in students' understanding that is abstract in the subjects of algorithms and programming. For this reason, the purpose of this study is to develop a DIVA Learning Management System model that has effectiveness. The methodology used is quasi experimental design in the form of nonequivalent pretest-posttest control group design. This study found the DIVA Learning Management System learning model with the syntax: a) Display; b) Information Search; c) Virtual Problem Solving; and d) Appraisal, and products from: (1) DIVA learning management system learning model (2) learning tools; (3) modules; and (4) learning media. Analysis of research data shows the learning model DIVA Learning Management System In the effectiveness test of media use for lecturers 92.3% is effectively used and for student learning outcomes with pre-test and post-test test scores can be seen from the achievement score of each respondent. The gain score results indicate the achievement score is at the level of 0.486 with the interpretation that overall an increase in scores after being given treatment to respondents. Based on the results of the data analysis above, it can be concluded that the model developed meets the feasibility to be used.